2018
DOI: 10.1155/2018/3685948
|View full text |Cite|
|
Sign up to set email alerts
|

Epithelial Cells Attenuate Toll-Like Receptor-Mediated Inflammatory Responses in Monocyte-Derived Macrophage-Like Cells to Mycobacterium tuberculosis by Modulating the PI3K/Akt/mTOR Signaling Pathway

Abstract: Both alveolar macrophages (AMs) and alveolar epithelial cells (AECs) are main targets of Mycobacterium tuberculosis (M. tuberculosis (Mtb)). Intercellular communications between mucosal AECs and AMs have important implications in cellular responses to exogenous insults. However, molecular mechanisms underpinning interactions responding to Mtb remain largely unknown. In this study, impacts of AECs on Toll-like receptor- (TLR-) mediated inflammatory responses of AMs to Mtb virulent strain H37Rv were interrogated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…In healthy human airways and alveolar sacs, epithelial cells constitute a surface of approximately 70 m 2 . 14 The epithelial cells may contribute indirectly to host response by enhancing the phagocytosis of Mtb in macrophages or contribute directly to host response against infection by releasing chemokines and antimicrobial peptides 15–17 . To investigate the immunoregulatory roles of Andro in the lungs during Mtb infection, a co‐cultural system of epithelial cells A549 and monocytic cells THP‐1 was established to mimic the microenvironment of the lungs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In healthy human airways and alveolar sacs, epithelial cells constitute a surface of approximately 70 m 2 . 14 The epithelial cells may contribute indirectly to host response by enhancing the phagocytosis of Mtb in macrophages or contribute directly to host response against infection by releasing chemokines and antimicrobial peptides 15–17 . To investigate the immunoregulatory roles of Andro in the lungs during Mtb infection, a co‐cultural system of epithelial cells A549 and monocytic cells THP‐1 was established to mimic the microenvironment of the lungs.…”
Section: Resultsmentioning
confidence: 99%
“…Besides macrophages, lung epithelial cells have also been found to play a major role in the immune response and pathogenesis of infection. Lung epithelial cells perform a variety of physiological functions, including the regulation of surfactant metabolism, ion transport, and alveolar repair 14–16 . A recent study revealed that lung epithelial cells activated by Mtb‐infected macrophages expressed high levels of anti‐mycobacterial peptides, defensins, and S100‐family members 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLRs are mainly expressed on the membranes of immune cells including macrophages, dendritic cells, T cells, and B cells [17][18][19][20][21][22]. Moreover, TLRs are also found in non-immune cells, such as endothelial and epithelial cells, adipocytes, and cardiomyocytes [23][24][25][26][27]. TLRs predominantly occur on the cell surface, while TLRs 3, 7, 8, and 9 are expressed inside cells [3].…”
Section: Introductionmentioning
confidence: 99%
“…6 illustrates this using the example of SNPs within and proximal to gene loci associated with PI3K/AKT signalling, which based on IPA data mining for bAM DE genes was a highly activated pathway, particularly at 24 hpi. In this regard, previous work has shown that macrophage PI3K/AKT signalling is key to a range of cellular processes associated with host-pathogen interaction in MTBC infections, including modulation of cell death pathways, manipulation of signalling downstream of TLRs, and initiation of granuloma formation (Maiti et al 2001;A et al 2012;Cho et al 2013;Liu et al 2016;Brace et al 2017;Yang et al 2018). We have also recently demonstrated that genes encoding protein products embedded in the PI3K/AKT pathway are primary targets for chromatin modifications that substantially alter bAM gene expression in response to M. bovis infection (Hall et al 2020).…”
Section: Discussionmentioning
confidence: 99%